Dinámica demográfica de la provincia Santiago de Cuba: un reto para el desarrollo territorial / Demographic dynamics of the province of Santiago de Cuba: a challenge for territorial development - Iliana Benítez Jiménez; Wilder Naranjo Sánchez; Georgina Garzón Morales (Novedades en Población, 2020)
This article describes and evaluates the demographic dynamics that Santiago de Cuba province presents today, as well as some challenges imposed by this dynamic for territorial development. For this evaluation, the measures and goals of the Program of Action of the International Conference on Population and Development of Cairo 1994 and its follow-up on the Regional Agenda on Population and Development of Montevideo 2013, assumed by Cuba as signatory of both documents, are taken as reference. Rate calculations and other indicators were made from data extracted from publications of the National Bureau of Statistics and Information of Cuba, and other sources at the provincial level. Some of them were graphed for their comparative analysis in selected years and with respect to Cuba. It was obtained that the demographic dynamics of the province is characterized by aging of its population, low fertility, low mortality especially child mortality, three sustained negative migratory balance and presence of a labor reserve mainly in the female population. As main conclusions were obtained that Santiago de Cuba requires development programs aimed at the best use of their labor resources, which propitiate higher labor productivity which results in better living conditions of its population to meet sustainable development criteria the particularities of its demographic dynamics, and that allow it to continue fostering the social policies that have propitiated the achievements that it exhibits today.